From Ancient to Islam: A Political Philosophy Perspective on The Sundanese Triumvirate - Mustapa, Hasan; Gozali, Nanang; Naan, Naan (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
Political leadership in Sundanese civilisation has existed since the 15th century. Although the mechanics of power transition have evolved ideologically, Tri Tangtu Di Bumi, a philosophical ideal of leadership, is still embedded in Sundanese society's social structure. This knowledge has evolved from the ancient (Sunda Wiwitan) Hindu age to Islam. This study investigates Tri Tangtu di Bumi as a manifestation of Sundanese political philosophy. The method used in this study is a philosophical examination of Sundanese society's triumvirate notions. According to the research findings, Tri Tangtu di Bumi is identical to Trias Politica. This leadership style delegates political power and legitimacy to three individuals: Prabu, Rama, and Resi. Prabu symbolises the government and Rama represents people's voices. Meanwhile, Resi mostly serves as a mediator and judge. Tri Tangtu's spirit can still be found in the lives of the Baduy, Banten, Kampung Naga, Tasikmalaya, and Ciptagelar tribes of Sukabumi today.Â